Building the field of health policy and systems research: An agenda for action - Bennett, S.; Agyepong, I.A.; Sheikh, K.; Hanson, K.; Ssengooba, F.; Gilson, L. (PLoS Medicine, 2011)
The lack of clarity and shared understanding regarding the scientific foundations of Health Policy and Systems Research (HPSR) [1] potentially has very negative consequences for the field [2]. Disagreement over the value of different types of theoretical frameworks and research methods can lead to inappropriate evaluations of research proposals, contradictory reviews of the same paper, and delays in publication. Excessive time may be spent communicating broad frameworks to other researchers within HPSR, inhibiting progression to more detailed and specific conversations. Communication barriers may discourage inter-disciplinary collaboration, driving researchers back to their disciplinary safety zones, and creating potential for conflict that may discourage younger researchers who may be less secure in their career from staying in the field. As the second paper in this series concluded [1], there is an urgent need to build understanding across disciplinary boundaries. This final paper in the “Building the Field of HPSR” series turns to practical questions concerning how to remove structural barriers that currently inhibit the development of the HPSR field and thus unlock HPSR capacities. HPSR suffers from many of the same problems as other branches of health research in low- and middle-income countries (LMICs): major imbalances between the resources available in high- versus low- and middle-income contexts [3], acute shortages of skilled researchers (especially senior ones), and relatively few organizations that house HPSR expertise [4]. Historically, low levels of funding for HPSR compared to clinical or biomedical research have compounded these problems. Many papers provide relevant recommendations to address health research capacity issues in LMICs [5]–[8]. However, there is also a nexus of issues specific to HPSR that currently constrains development of the field. This paper builds on the analysis of the previous papers in this series [1],[9] to investigate the practical problems faced and then develops an agenda for building the HPSR field.